Quantum Computing Analysis in Electricity Circuit Using Python - Satria, Andy; Ramadhani, Fanny (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2022)
This study aims to determine the quantum computing analysis in electrical circuits using python ptogram. Python is a programming language that can execute a number of multi-use instructions directly (interpretive) with the object orientation method. Python is the easiest programming language to understand. Python was created by a Dutch programmer named Guido Van Rossum. In the digital era, all professions related to technology and computers are considered promising in the future, one of which is programmer. There are many things you can create while pursuing the programmer world, such as software, smartphone applications, GUI programs, CLI programs, Internet of Things, games and others. Where quantum computing has inspired countless scientists, physicists and computer scientists. The development of the field of quantum computing can be seen from several demonstration experiments in the last two decades. Quantum information processing is a field that includes quantum computation, quantum cryptography, quantum communications, and quantum games, this field brings with it the idea of using quantum mechanics more than classical mechanics to model information processing. Quantum computing theory is not about changing the physical substrate on which computations are made from classical to quantum, but rather changing the idea of computing itself. This change can be seen from the change in the basic unit of calculation on the computer, namely the bit, which is changed to the quantum bit or qubit.